2018
DOI: 10.1007/s12105-018-0995-2
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Carcinoma of the Thyroid Gland: Report of a Highly Aggressive Case Clinically Mimicking Undifferentiated Carcinoma and Review of the Literature

Abstract: After being described in the salivary glands as a malignancy with features essentially identical to those of the breast, secretory carcinoma (SC) (formerly mammary analogue SC) has now been identified in other sites including the skin, lung, and thyroid gland. In the breast, SC has a relatively favorable prognosis. Likewise when arising in the salivary glands, it is generally considered to be a low to intermediate grade carcinoma; however, there is a range of clinical behavior with occasional patients dying of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…As a member of the new classification of salivary gland malignant tumors, it was officially listed in the WHO Head and Neck Tumor Classification (4 th edition) and referred to as secretory carcinoma. SCSGs of other organs have also been reported, such as the minor salivary glands around the sinuses ( 7 ), lips ( 8 ), and buccal mucosa ( 9 ), as well as the thyroid gland ( 10 ) and lungs. It often presents as a cystic-solid mass and the boundary is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the new classification of salivary gland malignant tumors, it was officially listed in the WHO Head and Neck Tumor Classification (4 th edition) and referred to as secretory carcinoma. SCSGs of other organs have also been reported, such as the minor salivary glands around the sinuses ( 7 ), lips ( 8 ), and buccal mucosa ( 9 ), as well as the thyroid gland ( 10 ) and lungs. It often presents as a cystic-solid mass and the boundary is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the junction is between Exon 5 of ETV6 and Exon 15 of NTRK3. Since the original series, SC has been subsequently reported in non-salivary gland sites such as skin, thyroid gland, eyelid, lung, as well as in the sinonasal tract [5][6][7][8][9][10]. Recently, bona fide salivary gland SC with ETV6-RET and ETV6-MET translocations have been described, thus expanding the molecular profile of SC beyond the ETV6-NTRK3 translocation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that this type of carcinoma can arise in the salivary glands, thyroid gland, lacrimal glands, and the skin 6‐8 . Fusion genes other than ETV6‐NTRK3 have been reported in secretory carcinomas of different organs, including ETV6‐RET , ETV6‐MET , and the dual fusion of ETV6‐NTRK3 and ETV6‐MAML3 6,7,9‐12 …”
Section: Discussionmentioning
confidence: 99%